Pemberdayaan Masyarakat Dalam Mengelola Terong Menjadi Produk Makanan Di Desa Lomaya - Hatu, Rauf A.; Hatu, Dewinta Rizky R. (Sosiologi Jurnal Penelitian dan Pengabdian Kepada Masyarakat, 2023)
Most of the people of Lomaya Village have a background as farmers and in every community environment they grow eggplant plants as a vegetable for personal consumption, but the Lomaya Village KKN team provides innovation and creation for eggplant management so that it can be used as a source of business ideas for the people of Lomaya Village. And it is hoped that it can have a positive impact on the people of Lomaya Village, especially helping the community's economy because the people of Lomaya Village on average have low incomes so the community needs social assistance. Therefore, the Lomaya Village KKN team implemented an additional program, namely community empowerment in managing eggplant into a food product, namely crispy eggplant in Lomaya Village. The methods used in this research were initial observation, FGD (Forum Group Discussion), lectures and training. The importance of carrying out this additional program is so that it can increase the community's knowledge and creativity regarding the use or management of natural resources in the surrounding areas and can help the economy of the Lomaya Village community.